Validity and Reliability of Physical Sports and Health Education's Learning Assessment of Self Defense Material for Class VII Junior High School Student - Putri Martyanti, Andini; Dona Sandy Yudasmara; Zihan Novita Sari (Journal Sport Science Indonesia, 2024)
Instruments adhering to appropriate standards are crucial in gauging the conclusive outcomes of learning activities. This ensures that student learning achievements are accurately identified, serving as evaluation benchmarks for subsequent educational programs. The present research endeavors to develop an assessment instrument for Physical Education and Health (PJOK) learning, specifically focusing on self-defense material designed for seventh-grade junior high school students. This instrument is envisaged as a valuable tool to assist educators in conducting assessments, leading to the optimization of learning skills evaluation outcomes. The research methodology employs the Research and Development approach, referencing the ADDIE development model. The analysis stage involves observation and interviews, instrument design, product development, as well as Focus Group Discussions (FGD) with learning evaluation experts. Additionally, instrument product trials are conducted to examine validity and reliability. The research involves 66 seventh-grade junior high school students as participants. The validity test was carried out using the Reproducibility Coefficient and Scalability Coefficient according to the Guttman scale test, while the reliability test used Kuder Richardson (K-R) 20. The validity test results showed that all variables had values ​​> 0.90 for the reproducibility coefficient and > 0.60 for the scalability coefficient so it is said to be valid. The reliability test results showed a value of > 0.60 for K-R 20 so it is considered reliable. In conclusion, the PJOK learning assessment instrument for self-defense material emerges as a reliable and valid tool. Educators can confidently integrate this instrument into their assessments, leveraging its proven to be valid and reliable.